+0  
 
+1
309
1
avatar+232 

The terms of a particular sequence are determined according to the following rules:
* If the value of a given term is an odd positive integer s, then the value of the following term is 3s-9
* If the value of a given term is an even positive integer l, then the value of the following term is 2t-7.
Suppose that the terms of the sequence alternate between two positive integers (a, b, a, b, ...). What is the sum of the two positive integers?

 Mar 22, 2019
 #1
avatar+6192 
+1

\(\text{suppose }a \text{ is odd}\\ b = 3a-9\text{ is even}\\ a = 2(3a-9)-7 = 6a-25\\ 5a=25\\ a=5,~b = 6,~a+b=11\)

 

\(\text{suppose }a \text{ is even}\\ b = 2a-7\text{ is odd}\\ a = 3(2a-7)-9= 6a-30\\ 5a=30\\ a=6,~b=5,~a+b=11\)

.
 Mar 23, 2019

13 Online Users

avatar